ANALYSIS OF CLINICAL AND LABORATORY INDICATORS OF MYOCARDITIS AND MYOPERICARDITIS IN PATIENTS WITH COVID-19. (International journal of artificial intelligence, 2026)
In December 2019, a new respiratory infection caused by a previously unidentified strain of coronavirus, named SARS-CoV-2, was identified in China. This virus belongs to the Coronaviridae family, Nidovirales, and is characterized by a pleomorphic structure with crown-like spikes on its surface, which is why it was named "coronavirus". The size of the viral particles varies from 80 to 160 nanometers, and the genome length, expressed as positive-sense RNA, ranges from 27 to 32 kilobases. The emergence of SARS-CoV-2 led to a global pandemic, named COVID-19.